Enhancing Feed Management Practices within the "Tani Agung" Beef Cattle Farming Cooperative in Dumajah Village, Bangkalan Regency - Mashudi, Mashudi; Bisri, Mohammad; Muluk, Mujibur Rahman Khairul; Muttaqin, Syariful; Ndaru, Poespitasari Hazanah; Kartika, Aprilia Dwi; Herlina, Herlina (Journal of Innovation and Applied Technology, 2025)
The Doktor Mengabdi Program in Dumajah Village aims to address challenges faced by the Tani Agung farmers group through five key strategies: (1) enhancing farmers' knowledge via extension services and training in good cattle farming practices; (2) increasing feed availability by promoting the cultivation of superior forage such as elephant grass, odot grass, and indigofera; (3) improving feed quality through ammonia treatment of agricultural waste to optimize local resources; and (4) implementing feed management techniques, including flushing and steaming-up for breeding cattle. Program activities include training sessions, forage planting, practical workshops on ammonia-treated feed production, and the adoption of Mini Feedmill technology for Total Mixed Ration (TMR) production. The program results in improved farmer knowledge, enhanced feed quality and availability, and increased livestock productivity, ultimately boosting farmer income and welfare, supported by the establishment of a Mini Feedmill facility.